Influência de adjuvantes e chuva simulada na deposição e otimização da dose de herbicidas para controle de plantas daninhas - Argioli, Agatha da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Maximizar a eficiência de controle de plantas daninhas, com o mínimo possível de contaminação ambiental e de forma econômica, é o maior desafio envolvido na aplicação de defensivos agrícolas. Essa pesquisa teve como objetivo verificar como o uso de adjuvantes agrícolas e chuva simulada podem afetar a deposição e a fitotoxidade na aplicação de herbicidas pós-emergentes em plantas daninhas. Os tratamentos consistiram na pulverização do corante Azul Brilhante (de 1,5 g L-1) associado com herbicidas em plantas de Euphorbia heterophylla (L.) e Digitaria insularis (L.) Fedde. Os valores de deposição em µL g-1 de matéria seca da parte aérea (MSPA) foram submetidos à análise de variância e as médias comparadas pelo teste Scott-Knott (p<0,05). Para análise de uniformidade da deposição, os dados foram ajustados à análise de regressão pelo modelo Logístico através do programa estatístico R. Para verificar o efeito das diferentes técnicas de aplicação na fitotoxidade das plantas foram pulverizados herbicidas em diferentes concentrações da dose comercial registrada para cada planta daninha. As avaliações foram constituídas pela porcentagem visual de fitotoxidade e da MSPA. Com base nos resultados encontrados os maiores valores de deposição foram proporcionados pelo adjuvante Fixade e as maiores reduções da massa seca da parte aérea das plantas daninhas foram observadas quando a simulação de chuva foi realiza nos maiores intervalos de tempo.

The optimization of weed management efficacy while simultaneously mitigating environmental impact and cost remains a pivotal challenge within the domain of agricultural pesticide utilization. We designed research to delve into the potential ramifications of incorporating agricultural adjuvants and simulated rainfall within the context of post-emergent herbicide application, with the objective of achieving efficacious weed control. The experimental protocol encompassed the application of Brilliant Blue dye, calibrated to a concentration of 1.5 g L-1, in conjunction with selected herbicides, onto distinct weed species: Euphorbia heterophylla L. and Digitaria insularis L. To assess deposition efficiency, precise measurements were undertaken, quantifying the levels in terms of µL g-1 of dry above-ground biomass (MSPA). These measurements were subjected to a statistical analysis employing variance examination, followed by the application of the Scott-Knott test, with a significance threshold set at p-value < 0.05. In parallel, the uniformity of deposition patterns was scrutinized utilizing a Logistic regression model, implemented through the R programming language. A vital facet of this study encompassed the evaluation of divergent application techniques and their distinct impacts on phytotoxicity. This intricate exploration involved the methodical administration of herbicides at varying concentrations, calibrated relative to the commercially registered doses for the respective target weed species. The comprehensive evaluation included critical metrics such as the visual percentage of phytotoxicity and MSPA. The results yielded intriguing insights. Notably, the application of the Fixade adjuvant demonstrated a substantial potential for augmenting deposition efficiency, thereby amplifying the overall effectiveness of the herbicidal application process. Equally captivating was the observation that the introduction of simulated rainfall at extended intervals emerged as a compelling variable, eliciting substantial reductions in the dry above-ground biomass of the targeted weed species. In essence, this study unveils the dynamic interplay between agricultural adjuvants, simulated environmental influences, and the application of post-emergent herbicides. Through a deconstruction and systematic evaluation of these pivotal components, our research contributes substantively to the advancement of precision-driven strategies for effective weed management.
Influence of adjuvants and simulated rain on deposition and herbicide dosage optimization for weed control
Keywords: Tecnologia de aplicação; Controle químico; Retenção da pulverização; Digitaria insularis; Euphorbia heterophylla; Application technology; Chemical control; Spray retention